Effects of Whole Body Vibration Exercise associated with Quadriceps Resistance Exercise on functioning and quality of life in patients with knee osteoarthritis: a randomized controlled trial. (November 2016) - Wang, Pu; Yang, Lin; Liu, Chuan; Wei, Xiaofei; Yang, Xiaotian; Zhou, Yujing; Jiang, Hua; Lei, Zhongjie; Reinhardt, Jan D.; He, Chengqi
Objective: To determine effects of Whole Body Vibration Exercise (WBVE) associated with quadriceps resistance exercises (QRE) versus QRE only on pain, physical function, biomarkers in serum and urine, activities of daily living (ADL), and quality of life in patients with knee osteoarthitis (OA). Design: Randomized-controlled trial . Setting: Rehabilitation medicine outpatient department of West China Hospital, Chengdu, Sichuan, People's Republic of China. Subjects: Forty-nine patients were assigned to WBVE+QRE and 50 to QRE . Main outcome measures: Primary outcomes included pain assessed with visual analogue scale (VAS), Timed up & go test (TUG), 6-min walk distance test (6MWD), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). Secondary outcomes comprised range of motion, muscular strength, serum COMP and urinary CTX-II, Lequesne Index (LI), and SF-36. All outcomes were analyzed with mixed effects regression. Results: Compared with QRE, WBVE+QRE showed signiﬁcantly greater improvement in VAS at 4weeks ( p =0.03), in VAS ( p <0.01), 6MWD ( p =0.01), WOMAC pain ( p =0.01), and WOMAC physical function ( p =0.02) at 16 weeks, and in all primary outcomes at 24 weeks (all p <0.01). Conclusion: Over a six months period, WBVE in combination with QRE was superior to QRE in most outcomes.